Cyclin D1 and Chemotherapy Response - Cosphiadi Irawan; Rahmat Cahyanur (National Cancer Center - Dharmais Cancer Hospital, 2021)
Cyclin D1 is a protein that plays a role in the transition from the G1 to S phase of the cell cycle. Cyclin D1 expression has been found to increase in various malignancies and, in many studies, was associated with tumor growth, stage, lymph node involvement, distant metastases, and poor prognosis. Until now, studies on the association of cyclin D1 expression level with chemotherapy response have shown different results. An in-depth understanding of the cell cycle will allow doctors to develop target therapies that work when specific interventions are carried out at certain stages. Some studies reported that cyclin D1 expression was inversely related to chemotherapy response, while others showed opposite results. A significant number of studies have attempted to elucidate this ambiguous effect of cyclin D1. The suggested mechanism involves the difference of cancer cell types, the effect of chromosome instability in a few malignancies, trigger to an excessive DNA repair protein expression stimulus, and the response to DNA damage severity. The ambiguous effect of cyclin D1 towards chemotherapy was thought to arise from the difference in tumor type, chemotherapy agents used, and cell damage severity caused by cytostatics as per different research works. More in-depth research with parallel evaluation of other possible mechanisms such as DNA repair should elucidate the reason behind the inconsistent findings.